Cooperative learning: a new application of problem-based learning in mental health training. - Bahar-Ozvaris S; Cetin FC; Turan S; Peters AS (Medical Teacher, 2006)
Interaction in problem-based learning (PBL) tutorials is not necessarily cooperative, which may account for variation in learning outcomes. Therefore, a cooperative assessment structure was introduced in a PBL course and the difference examined between this method and individual, lecture-based learning in mental health training. Experimental student groups gained more knowledge between pre- and post-test than did control groups, and the experimental students who scored low on the pre-test made the greatest gains. Groups that reported greater cooperation tended to have higher achievement scores. Experimental students felt that cooperation helped them learn but it also took more time and was sometimes chaotic.